(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2011)
This paper includes a study of the performance of Al-Nassiriyah thermal power plant condenser. Which includes a calculations of the main variables of condenser (heat transfer,condensation rate, overall heat transfer coefficient and vapour pressure) by applying two dimensional mathematical model and depending on the empirical equations of heat transfer.Comparison was made between the theoretical results for Al-Nassiriyah thermal power plant condenser before operation it (standard power plant) with practical data which taken from the plant for the second unit in year 2007. The comparison showed that there was a large difference between theoretical results and the values taken from the plant as a result to the effect of operation conditions.